2010
DOI: 10.1159/000313815
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anterior Chamber Depth Using Visante Optical Coherence Tomography, Slitlamp Optical Coherence Tomography, IOL Master, Pentacam and Orbscan IIz

Abstract: Aims: To assess and compare the anterior chamber depth (ACD) by different anterior segment imaging techniques. Methods: Eighty healthy eyes of 40 patients were recruited, and 3 consecutive measurements of ACD were determined prospectively utilizing Visante optical coherence tomography (OCT), slitlamp (SL) OCT, IOL Master, Pentacam and Orbscan IIz. The statistical significance of interdevice differences between measurements was evaluated by one-way ANOVA and Bland-Altman analysis. The repeatability of 3 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
3
19
0
2
Order By: Relevance
“…Our findings are in agreement with those of Dinc et al, 18 who measured the ACD from the corneal endothelium to the anterior surface of the lens and found a mean ACD of 3.33 mm using the IOLMaster PCI biometer, 2.93 mm using the Pentacam Scheimpflug camera, and 2.98 mm using the Visante OCT device (Carl Zeiss Meditec) (n Z 40). In our study, the IOLMaster PCI measurements were longer than the Pentacam Scheimpflug measurements (3.71 mm versus 3.24 mm; 95% CI, 0.433-0.517), whereas the PCI true measurements were shorter than the Scheimpflug device measurements (3.24 mm versus 3.18 mm; 95% CI, 0.018-0.102).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in agreement with those of Dinc et al, 18 who measured the ACD from the corneal endothelium to the anterior surface of the lens and found a mean ACD of 3.33 mm using the IOLMaster PCI biometer, 2.93 mm using the Pentacam Scheimpflug camera, and 2.98 mm using the Visante OCT device (Carl Zeiss Meditec) (n Z 40). In our study, the IOLMaster PCI measurements were longer than the Pentacam Scheimpflug measurements (3.71 mm versus 3.24 mm; 95% CI, 0.433-0.517), whereas the PCI true measurements were shorter than the Scheimpflug device measurements (3.24 mm versus 3.18 mm; 95% CI, 0.018-0.102).…”
Section: Discussionsupporting
confidence: 92%
“…However, none of these studies compared ACD measurements by all 4 devices at the same time under identical conditions using a large enough sample. For example, studies have reported that the Pentacam device offered good intraobserver repeatability 25,26 and interobserver reproducibility for ACD measurements. 26 In another study by Chen et al, 19 excellent intraobserver repeatability was shown for ACD measurements using the Sirius system, with a repeatability limit of 0.02 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmaların çoğunda Pentacam (Oculus-Optikgerate GmbH-Wetzlar-Germany) sistemi kullanılmıştır. 10,[13][14][15][16] Her iki cihazda da açı hesaplamaları ham sayısal görüntülerin (verilerin) interpolasyon veya ekstrapolasyon yöntemleriyle analiz edilmesinden elde edilir. Sirius sisteminde Nazal ve temporal kadranları kesen yedi aksiyel Scheimpflug kesitin ham görüntülerinden elde edilen ÖKA ortalamaları ile OÖKA elde edilir.…”
Section: Discussionunclassified